PENGARUH PEMBERIAN SUSU TERHADAP KADAR KALSIUM DARAH DAN KEPADATAN TULANG REMAJA PRIA - Suryono Suryono; Budi Setiawan; Drajat Martianto; Dadang Sukandar (Media Gizi dan Keluarga, 2007)
Milk consumption during adolescence is considered an early means of preventing osteoporosis in adults. Osteoporosis is a systemic skeletal disease characterized by low bonedensity and microarchitectural deterioration of bone tissues, with a consequent increase in bone fragility and suspectibility to fracture. Augmenting bone mass during adolescence has beensuggested as a strategy to prevent osteoporosis. because adolescents may represent the final opportunity for substantially increasing bone mass before skeletal consolidation. The purpose of this Study was 10 determine effects of fresh and high calcium milk on blood calcium concentraJion and bone density. Variables measured in this study were blood calciumconcentration. bone density of spine and bone density of whole body. The study using 55 adolescent boys thal had 17 to 19 years old (students of TPB [PB) and was conducted at TPBIPB dormitory in four months. The design of this study is nesled randomized design with two factors are kind of mil (fresh milk, high calcium milk) and volume of each kind of milk (250 ml,500 ml, 750 mI). Results of the study indicated that fresh and high calcium milk in this research not significant effects (P>0.05) on blood calcium concentration and bone density of whole body.But, high calcium milk consunlption was able to increase bone density. It was found that high calcium consumption shawed very highly significant effect (P<O.OI) on bone density of spinewith 1.79% contributions. Based on general linear model equation. bone density of trunk can be estimated by high calcium milk consumption.